The Relationship Between Body Mass Index and Physical Fitness Level with PJOK Learning Outcomes in the Odd Semester of 2024/2025 for 8th Grade Students at SMP Negeri 2 Jabung, Malang Regency. - Izzudin Nafi’an Syah Kayril; Siti Nurrochmah (Universitas Hamzanwadi, 2025)
The success of physical education learning does not only depend on pedagogical factors, but also on the physical condition of students. However, the relative contribution between nutritional status (in Body Mass Index) and physical fitness levels to physical education learning outcomes has not been quantitatively measured in the specific context of schools with adequate facilities, such as at SMP Negeri 2 Jabung. This study aims to analyze the relationship and measure the effective contribution of BMI and physical fitness to the PJOK learning outcomes of eighth-grade students. This quantitative study uses a correlational design involving 42 male students as samples (purposive proportional random sampling technique). BMI data were obtained from anthropometric measurements, physical fitness was measured using the Indonesian Physical Fitness Test (TKSI), and learning outcomes were taken from report card scores. Data analysis used Pearson's correlation and multiple regression. The results of this study found a significant positive relationship between BMI (r=0.418) and physical fitness (r=0.787) with PJOK learning outcomes. Regression analysis showed that both variables together contributed effectively by 66.4%, with physical fitness as the dominant contributor (effective contribution of 57.2%; relative contribution of 86.2%). Conclusion: Physical fitness is a key factor that determines PJOK learning outcomes more than BMI in students at SMP Negeri 2 Jabung.